PEMAHAMAN RELASIONAL SISWA DALAM MENYELESAIKAN SOAL PROGRAM LINEAR DI KELAS XI MAN 2 PONTIANAK - Saparida, Cici; Yusmin, Edy; Nursangaji, Asep (Universitas Tanjungpura, 2022)
Abstract This study aims to find out students' relational understanding linear program materials in the class XI MAN 2 Pontianak . This form of quantitative descriptive research, for the data collection techniques used are test techniques and indirect communication techniques. For the data-mining techniques used is a matter of tests and interviews. Student relational understanding in this study is measured using linear program material consisting of 6 essay questions. The relational understanding referred to in this study is the students' ability to solve the linear program problem by using appropriate procedures and knowing why it is used. It is known that students who have the relational understanding ability to solve a problem is that students have the prerequisite ability to solve linear programs that fall into a very good category, to be able to do overall procedures in ending linear programs in excellent categories, and to get the right results and provide logical reasons for completing linear programs. Overall students have a high relational understanding with very good percentages. Keywords: Relational Understanding, Conceptual Understanding and Procedural Understanding, Linear Program